Program Pelatihan Menggosok Gigi Dalam Meningkatkan Keterampilan Bina Diri Siswa Tunagrahita di SLB se-Kota Padang - Safaruddin, Safaruddin; Fatmawati, Fatmawati; Budi, Setia (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
Education is a basic right that every child in general must have without exception. Academic, social and emotional abilities can develop well through education. The curriculum used in Indonesia at the moment was the 2013 curriculum. One of the schools that carries out educational activities was the Extraordinary School (SLB). SLB was one of the place whom expected to develop the development of mentally retarded children. Through Special School, mentally retarded children got academic and non-academic education that suits their needs. One of the skills that must be taught is the ability to brush your teeth. Retarded students in the moderate category still find it difficult to brushed parts of teeth that were located inside such as right and left teeth and inner teeth. In addition to the position of the teeth, the frequency and time of tooth brushing was also a problem for the mentally retarded child. based on the activities that have been carried out, it appears that the ability of teachers to brush their teeth has improved, this is expected to help their students to brush their teeth properly.